The Role of Advanced Prosthetic Technologies in Enhancing Patient Mobility and Independence: Implications for Nursing Practice in Orthopedic Surgery - Almutairi , Abdullah Naif Dari; Alshahrani, Wasmiah Abdullah Faleh; Almansour , Hayyan Abdul Aziz; Alotaibi, Khalid Mahmes; Alqasmi , Layla Hasan; Sheikh, Majdi Motia; Khormi, Areej Mohammed Essa; Alzeed, Tahani Suliman; Al Rashidi, Hind Mohammed; Almotyre, Fahad Abdullah; Alotaibi, Bander Mansour B; Alsuliman, Abdulmajeed Mohammed; et al. (Journal of Ecohumanism, 2024)
Background: The integration of advanced prosthetic technologies into orthopedic surgery has emerged as a pivotal advancement aimed at enhancing patient mobility and independence. These technologies not only improve surgical outcomes but also significantly impact patient quality of life post-operation. Methods: This review examined recent literature across multiple databases, including PubMed, Scopus, and MEDLINE, focusing on studies published between 2021 and 2023. The search targeted keywords such as advanced prosthetic technology, patient mobility, independence, and implications for nursing care. Results: The findings indicate that advanced prosthetic technologies, including robotic-assisted surgeries and 3D-printed implants, have led to notable improvements in surgical precision and patient recovery times. Studies highlighted enhanced functional outcomes and reduced complication rates, resulting in increased patient satisfaction. However, the role of nursing professionals in the implementation and management of these technologies remains inadequately explored, presenting a gap in the current understanding of comprehensive patient care. Conclusion: The integration of advanced prosthetic technology in orthopedic practices presents significant opportunities for improving patient mobility and independence. However, further research is essential to delineate the specific roles and responsibilities of nursing professionals in this evolving landscape. By fostering effective collaboration between surgical teams and nursing staff, the full potential of these technologies can be realized, ultimately enhancing patient care outcomes